Community-acquired Haemophilus influenzae pneumonia – New insights from the CAPNETZ study. Issue 5 (May 2016) - ,; Krüger, S.; Frechen, D.; Knüppel, W.; Armari, I.; Stolz, D.; Suttorp, N.; Schütte, H.; Creutz, P.; Bauer, T.; Hecht, J.; Pankow, W.; et al.
Summary: Objectives: We aimed to identify clinical characteristics and to assess effectiveness of different initial antibiotic regimens in adult patients with community-acquired pneumonia (CAP) caused by Haemophilus influenzae . Methods: Characteristics were compared between patients with H. influenzae monoinfection versus CAP of other and unknown aetiology enrolled by the German prospective cohort study CAPNETZ. Impact of initial antibiotic treatment on "early clinical response" according to FDA criteria and overall clinical cure were analysed. Results: H. influenzae was found in 176 out of 2790 patients with pathogen detection (6.3%). Characteristics significantly associated with a H. influenzae CAP (p < 0.017) included purulent sputum, prior pneumococcal vaccination and respiratory co-morbidities. Early clinical response rates on day 4 did not differ between patients receiving any mono- versus combination therapy (85.9% versus 88%), but were numerically higher for regimens including any fluoroquinolone (96.7%) and lower under macrolide monotherapy (70%). Initial CURB-65 score and chronic liver disease were identified as negative predictors for "early clinical response". At day 14, overall clinical cure was 91.9%. Conclusions: H. influenzae was a common CAP pathogen, particularly in patients with previous pneumococcal vaccination and respiratory co-morbidities. Severity of illness and chronic liver disease were associated with a lower rate of "early clinical response". Highlights: Haemophilus influenzae ranks fourth among the most frequent pathogens in CAP. H. influenzae CAP appears to be a condition with a mainly benign outcome. Respiratory co-morbidity is the main risk factor of H. influenzae CAP. Overall early clinical response rates were 86%, but only 70% under a macrolide. Severity of illness and chronic liver disease predicted reduced early clinical response.